(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article describes the nomadic culture of the Kazakh people, and how it is reflected in the Kazakh cinematografe. The first part describes their way of life, laws and moral ethics. Nomadism is actualized as phenomenal and vast civilization that has incorporated a space of culture and religion of all Turkic peoples. Here is opened the entire encyclopedia of rich and extraordinary spiritual life of the Kazakh people, as well as the culture of the nomads, their traditions and rituals. In addition, we can immerse in the fascinating world of cinema on the example of the film «Kyz-Zhibek» where, in addition to its interesting plot, the characteristics of the personages and the mentality of the Kazakh people are revealed.